Analisis Kualitas Kerja Pegawai Tata Usaha Sekolah Menengah Pertama Negeri 1 Delitua - Risjalia, Poppy; SULAIMAN, FAHMI (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research was conducted to determine the quality of work possessed by employees at SMPN 1 Delitua. This study used a qualitative method with data collection techniques carried out through observation, unstructured interviews and documentation. based on observational interviews with administration employees, and staff, it appears that some employees also have good potential, and optimal work results, even though there are some obstacles they face when carrying out their duties but they remain enthusiastic in carrying out their work. Administrative staff of SMP N 1 Delitua have high enthusiasm, high enthusiasm is evidenced by good attendance when coming and going home according to working hours, quickly carrying out assignments when someone gives them assignments, administrative staff of SMP N 1 Delitua immediately do it and don't delay delay.